Analyzing a long dream series: what can we learn about how dreaming works? - Schredl, Michael (Taylor & Francis Group, 2024)
Analyzing a Long Dream Series provides an extraordinary insight into the richness and variability of dreams, considering over 12,000 dreams that have been recorded for more than 30 years.
Description based on publisher supplied metadata and other sources